A Diagnosis of the Local Administration Performance According to Satisfaction of the Local Citizens: A Case Study in Diyala Province – Iraq - Matook Abood Al-Mahdi*, Mohammed (Journal of Economics and Administrative Sciences, 2024)
Paper type: Research paperThe purpose of this research is to diagnose the reality of the provided local performance by the local government and its impact on the local citizens' satisfaction in one of the Iraqi provinces (Diyala Province). The problem of this research was most local citizens that were not satisfied with the local performance of local governments in providing public services in most Iraqi provinces. The research methodology was the descriptive analytical approach by knowing the views and opinions of a sample of the local citizens that contained 1200 participants, where the research conducted the questionnaire as the main instrument. The data were analyzed by using appropriate statistical methods such as frequencies, percentages, and simple regression coefficients through the statistical program (SPSS. V.26). Several significant results address the gap between the local performance and citizens' satisfaction, where the critical result was the level of public satisfaction with the local performance of the local government is extremely weak, and most of the citizens are unsatisfied. The practical and social implications of the research may improve and develop the skills and abilities of the members of local governments by enrolling them in programs and workshops, particularly in public relations, public administration, non-profit, strategic planning, and local administration to build stronger communication and interaction between members of the government and the local community with specialist universities and institutes could lead to raising the level of the local performance and public satisfaction.